OPTIMIZATION OF AN IONIZATION BASED VERTICALLY ALIGNED MWCNTS GAS SENSOR - ATIEH RANJBAR , KERMANY (2012)

(untitled)
The current solid state ionization-based gas sensors have high operating voltage that increases the operating risk factor and are relatively bulky. The dimensions and power requirement of these sensors can be optimized by using carbon nanotubes (CNTs) as the gas sensing element. An ionization-based gas sensor using aligned multi-wall carbon nanotubes (MWCNTs) array has been developed where its sensing properties such as the response time, selectivity, sensitivity, and breakdown voltages of different gases were investigated through the variation of electrode gap and gas concentration. The MWCNTs array was produced using CVD method. The structural and electrical characterization were carried out by using X-ray diffraction, transmission and scanning electron microscopy, Raman spectroscopy and Hall Effect to determine the suitability of the as-produced MWCNTs array as an effective sensing element. The aligned MWCNTs array was incorporated into the sensor configuration in the gas chamber for testing of gases namely argon, air, 2% of hydrogen in air, ammonia, and helium with electrode separation ranging from 80 pm to 150 pm. The CNTs array is found to be of highly directional multi-wall type, with good crystallinity (IdG - 0.75), typical diameter and length of 10 nm and 20 pm, and mobility and conductivity of 17.5l~o 3 cm2/Vs and 3 . 3 ~10 ' Slcm, respectively. It was proven that the breakdown voltage decreasing as the electrode spacing reduces from 150 pm to 80pm for all the gases among which helium was found to have the lowest breakdown voltage (119 V at 80 pm, 180 V at 150 pm) whilst air has the highest (249 V at 80 pm, 362 V at 150 pm). A reduction of more than 50% in the breakdown voltage, microsecond response time, highly sensitive and selective properties with room temperature operation had proven that the highly ordered MWCNTs array is an effective sensing element resulting in better performed gas sensor compared to the conventional solid-state sensors. Besides that, an average reduction of 15% in the breakdown voltage compared to non-aligned CNTs-based gas sensor confirmed the effect of alignment on the sensor performance.